ANALISIS PENGARUH IMPELLER OPEN SUDU 6 PADA POMPA SENTRIFUGAL MENGGUNAKAN SIMULASI CFD: ANALYSIS OF THE EFFECT OF THE 6 BLADE OPEN IMPELLER ON THE PUMP CENTRIFUGAL USING CFD SIMULATION - Muhammad Azmal Fahri (Jurnal Teknik Mesin, 2025)
Centrifugal pumps are very important equipment in various industrial applications, especially in the oil and gas and fluid processing industries. This pump works on the principle of moving fluid using centrifugal force generated by the impeller. Impeller design, including the number of blades and type, greatly influences pump performance. This research aims to evaluate the performance of an impeller with 6 open blades using Computational Fluid Dynamics (CFD) simulation. This simulation provides a detailed picture of impeller performance without requiring direct physical testing, thereby reducing costs and time in the development process. The research results show that the impeller with milk 6 provides optimal performance for industrial applications that require high heads and large capacities so that it can produce capacities close to manufacturer specifications with an efficiency of 69%. These results indicate that the open impeller is reliable for fluids with solids content.